Inferring gas-phase metallicity gradients of galaxies at the seeing limit: a forward modelling approach. Issue 2 (3rd March 2017) - Carton, David; Brinchmann, Jarle; Shirazi, Maryam; Contini, Thierry; Epinat, Benoît; Erroz-Ferrer, Santiago; Marino, Raffaella A.; Martinsson, Thomas P. K.; Richard, Johan; Patrício, Vera
Abstract: We present a method to recover the gas-phase metallicity gradients from integral field spectroscopic (IFS) observations of barely resolved galaxies. We take a forward modelling approach and compare our models to the observed spatial distribution of emission-line fluxes, accounting for the degrading effects of seeing and spatial binning. The method is flexible and is not limited to particular emission lines or instruments. We test the model through comparison to synthetic observations and use downgraded observations of nearby galaxies to validate this work. As a proof of concept, we also apply the model to real IFS observations of high-redshift galaxies. From our testing, we show that the inferred metallicity gradients and central metallicities are fairly insensitive to the assumptions made in the model and that they are reliably recovered for galaxies with sizes approximately equal to the half width at half-maximum of the point spread function. However, we also find that the presence of star-forming clumps can significantly complicate the interpretation of metallicity gradients in moderately resolved high-redshift galaxies. Therefore, we emphasize that care should be taken when comparing nearby well-resolved observations to high-redshift observations of partially resolved galaxies.